Answer:
x=7 valid solution
x=4 extraneous solution
Explanation:
sqrt( x-3) +5 = x
Subtract 5 from each side
sqrt( x-3) +5 -5= x-5
sqrt( x-3) = x-5
Square each side
(sqrt( x-3))^2 = (x-5)^2
Foil the right side ( x-5)(x-5) =x^2 -5x-5x+25 = x^2 -10x+25
x-3 = x^2 -10x+25
Subtract x from each side
-3 = x^2 -10x -x+25
Add 3 to each side
0 = x^2 -11x +25 +3
0 = x^2 -11x+28
Factor
0 = (x-7)(x-4)
Using the zero product property
x-7 =0 x-4=0
x=7 x=4
Check the solutions
sqrt( x-3) +5 = x
x=7
sqrt( 7-3) +5 = 7
sqrt(4) +5 = 7
2 +5 = 7 valid solution
x=4
sqrt( 4-3) +5 = 4
sqrt(1) +5 = 4
1 +5 = 4 not true extraneous solution